An Etymological and Terminological Review on Suicide - Nefise Ladikli; Itır Tarı Cömert (İbn Haldun Çalışmaları Dergisi, 2024)
Suicide is a public health issue with legal, medical, economic, social, and individual consequences. Simultaneously, it is a multidimensional phenomenon that requires examination from psychological and sociological perspectives in terms of cause-and-effect relationships. Over the years, numerous studies have been conducted on suicide using various methods; however, there is still a need for research in predicting suicide risk and effectively preventing suicide. Theoretical groundwork is required for the execution of these studies, necessitating an understanding of definitions and terminology. This review aims to exploring the origin of suicide word specifically in Turkish and English, examining the attempts to definition, and classification the suicide phenomenon.